Asthmatic Bronchial Matrices Determine the Gene Expression and Behavior of Smooth Muscle Cells in a 3D Culture Model - Ben Hamouda, Selma; Miglino, Maria Angélica; de Sá Schiavo Matias, Gustavo; Beauchamp, Guy; Lavoie, Jean-Pierre (Frontiers in Allergy, 2021)
Asthma is associated with increased deposition and altered phenotype of airway smooth muscle (ASM) cells. However, little is known about the processes responsible for these changes. It has been suggested that alterations of the extracellular matrix (ECM) contribute to the remodeling of ASM cells in asthma. Three-dimensional matrices allow the in vitro study of complex cellular responses to different stimuli in a close-to-natural environment. Thus, we investigated the ultrastructural and genic variations of ASM cells cultured on acellular asthmatic and control bronchial matrices. We studied horses, as they spontaneously develop a human asthma-like condition (heaves) with similarities to chronic pulmonary changes observed in human asthma. Primary bronchial ASM cells from asthmatic (n = 3) and control (n = 3) horses were cultured on decellularized bronchi from control (n = 3) and asthmatic (n = 3) horses. Each cell lineage was used to recellularize six different bronchi for 41 days. Histomorphometry on HEPS-stained-recellularized matrices revealed an increased ASM cell number in the control cell/control matrix (p = 0.02) and asthmatic cell/control matrix group (p = 0.04) compared with the asthmatic cell/asthmatic matrix group. Scan electron microscopy revealed a cell invasion of the ECM. While ASM cells showed high adhesion and proliferation processes on the control ECM, the presence of senescent cells and cellular debris in the asthmatic ECM with control or asthmatic ASM cells suggested cell death. When comparing asthmatic with control cell/matrix combinations by targeted next generation sequencing, only AGC1 (p = 0.04), MYO10 (p = 0.009), JAM3 (p = 0.02), and TAGLN (p = 0.001) were differentially expressed out of a 70-gene pool previously associated with smooth muscle remodeling. To our knowledge, this is the first attempt to evaluate the effects of asthmatic ECM on an ASM cell phenotype using a biological bronchial matrix. Our results indicate that bronchial ECM health status contributes to ASM cell gene expression and, possibly, its survival.